Antibiotic Use in Acne vulgaris: Pharmacological Perspectives and Emerging Resistance - A Brief Review - Pane, Yunita Sari; Hasanah, Nur (International Journal of Ecophysiology, 2025)
Background: Acne vulgaris (AV) is a chronic inflammatory skin condition that frequently affects adolescents and young adults. It is characterized by comedones, papules, pustules, and nodules. The primary etiological factors include hyperkeratinization, excessive sebum production, colonization of Cutibacterium acnes (C. acnes), and an inflammatory immune response. Objective: This review discusses the pharmacological aspects and challenges associated with the use of antibiotics in AV treatment, particularly in the context of rising antibiotics resistance. Methods: This mini-review was conducted using data collected from online academic databases, including Google Scholar, ScienceDirect, and PubMed. From an initial pool of 60 articles related to AV treatment,antibiotic mechanism, and resistance patterns, 31 publications (1999 – 2024) were selected based on relevance and quality. Results: The pathophysiology of AV is multifactorial, involving sebaceous hyperactivity, follicular hyperkeratinization, microbial colonization, and immune-mediated inflammation. Topical drugs (e.q., tetracyclines) remain central in AV management. However, increased antibiotic resistance, especially by C. acnes has compromised their efficacy. Combining antibiotics with agents like benzoyl peroxide (BPO) or topical retinoids may help mitigate resistance. Alternative treatments, including isotretinoin, hormonal therapies, and physical modalities, provide additional therapeutic options. Conclusion: Antibiotic use in AV treatment requires careful pharmacological consideration, balancing efficacy, safety, cost, and resistance risk. To preserve long-term effectiveness, antibiotics should be combined with non-antibiotic agents and used for limited durations. Tailoring treatment based on disease severity, location, and patient preference is essential for optimal outcomes.